Good university governance: experience from Indonesian university - Risanty Risanty; Sambas Ade Kesuma (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
The purpose of this paper is to discuss the concept of a good university governance. Particularly, this paper discuss the implementation of good governance in Indonesia and the principles used in achieving good governance in Indonesia. Education has developed from time to time and universities as higher education institutions also develop into a dynamic and modern institutions of knowledge. The concept of good university governance provides a guidance for the management of a university and the university should place itself in the middle of the public and the nation. The concept of university governance is originally derived from the good governance concept. The concept of university governance is a guideline for the university to achieve the vision and objectives as a professional institution. There are eight good university governance in Indonesia, namely transparency, accountability to stakeholders, responsibility, independence in decision making, fairness, quality assurance and relevance, effectiveness and efficiency, as well as non-profit. These principles need to be developed in all academic activities and the university management.